Resection of a thoracoabdominal ganglioneuroma via a retroperitoneal minimally invasive approach - Laura A. Galganski; Shinjiro Hirose; Payam Saadai (Elsevier, 2019)
A 10-year-old girl presented to her pediatrician with a history of cough and fever. A chest radiograph revealed a paraspinal mass. On cross-sectional imaging, the mass traversed the diaphragm, extending from T9 to L1 spinal levels with involvement of the T10-12 neural foramen. Vanillylmandelic and homovanillic acid levels were normal. On review of historical radiographs, the mass had increased in size. Thus, surgical resection was recommended for diagnosis and treatment.The patient was placed in left lateral decubitus position. The retroperitoneal space was accessed inferior to the twelfth rib. One 12 mm and two 5 mm ports were used. Development of the retroperitoneal space was achieved with both blunt dissection and a vessel-sealing device. The diaphragm was incised to resect the thoracic component of the mass. The tumor was adherent at the neural foramen and was resected flush with the spine. The diaphragm repaired primarily. She was discharged home on post-operative day four without complication. Pathology demonstrated a ganglioneuroma. The patient was well at her follow-up, and imaging one year post-operatively was without recurrence. No additional treatment was required.A laparoscopic retroperitoneal approach allows for a safe, minimally invasive resection of a thoracoabdominal mass without violation of the abdominal cavity. Keywords: Pediatric laparoscopic, Retroperitoneoscopic, Ganglioneuroma, Ganglioneuroblastoma, Neuroblastoma, Thoracoabdominal resection